2011
DOI: 10.1073/pnas.1018359108
|View full text |Cite
|
Sign up to set email alerts
|

Extranuclear protection of chromosomal DNA from oxidative stress

Abstract: Eukaryotic organisms evolved under aerobic conditions subjecting nuclear DNA to damage provoked by reactive oxygen species (ROS). Although ROS are thought to be a major cause of DNA damage, little is known about the molecular mechanisms protecting nuclear DNA from oxidative stress. Here we show that protection of nuclear DNA in plants requires a coordinated function of ROS-scavenging pathways residing in the cytosol and peroxisomes, demonstrating that nuclear ROS scavengers such as peroxiredoxin and glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(150 citation statements)
references
References 49 publications
4
145
0
1
Order By: Relevance
“…This underscores the potential importance of the cytosolic isoforms in coupling ascorbate and glutathione pools and is consistent with previous studies demonstrating the importance of cytosolic APX1 or GR1 in cat2-triggered responses (Mhamdi et al, 2010a;Vanderauwera et al, 2011) The importance of the cytosol in this context may be related to the peroxisomal location of the H 2 O 2 that becomes available when catalase is deficient, although decreased glutathione oxidation also was reported for single dhar1 and dhar2 mutants after exposure to high light (Noshi et al, 2017). DHAR3 may be more significant in chloroplastic processing, although our data provide little evidence that this isoform plays a specific role in response to paraquat-induced oxidative stress, which largely originates in this organelle (Supplemental Fig.…”
Section: Dhars Cooperate In Glutathione Oxidation Triggered By Oxidatsupporting
confidence: 73%
“…This underscores the potential importance of the cytosolic isoforms in coupling ascorbate and glutathione pools and is consistent with previous studies demonstrating the importance of cytosolic APX1 or GR1 in cat2-triggered responses (Mhamdi et al, 2010a;Vanderauwera et al, 2011) The importance of the cytosol in this context may be related to the peroxisomal location of the H 2 O 2 that becomes available when catalase is deficient, although decreased glutathione oxidation also was reported for single dhar1 and dhar2 mutants after exposure to high light (Noshi et al, 2017). DHAR3 may be more significant in chloroplastic processing, although our data provide little evidence that this isoform plays a specific role in response to paraquat-induced oxidative stress, which largely originates in this organelle (Supplemental Fig.…”
Section: Dhars Cooperate In Glutathione Oxidation Triggered By Oxidatsupporting
confidence: 73%
“…41 ROSderived DNA oxidation can lead to both the altered bases and the damaged sugar residues, resulting in DNA single-and double-strand breaks. 19 Although ROS were thought to be a major cause of DNA damage, 42 many studies draw such conclusions solely on the basis of changes of antioxidative enzyme activities, such as those of superoxide dismutase (SOD) and catalase (CAT) in plants, 43 and the direct determination of…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Therefore, the increase in the γ-H2AX level in the present study suggested that DNA damage became more serious with increasing exposure concentration of HBCD. ROS is thought to be a major cause of DNA damage (Vanderauwera et al, 2011). To further confirm whether the DNA damage in maize was induced by U OH generation, sodium benzoate, an U OH scavenger (Chang et al, 2005), was added to the exposure solution.…”
Section: Dna Damage Responses and Potential Toxicity Mechanismmentioning
confidence: 99%